(untitled) (Journal of Economic Research & Business Administration, 2023)
Annotation. The article discusses the problems of increasing the investment attractiveness of the regions of Kazakhstan. Based on the data of the Bureau of National Statistics of the Agency for Strategic Planning and Reforms of the Republic of Kazakhstan, the indicators of the dynamics of investments in fixed assets in the sectoral, technological and territorial context are analyzed and systematized. In Kazakhstan, there are noticeable imbalances and significant interregional differences in the level of gross regional product per capita. The presence of outsider regions requires an operational solution to the problem of increasing their investment attractiveness. Otherwise, further lagging behind the leading regions may result in negative consequences in the form of increased unemployment, lower incomes of the population, migration of the able–bodied part of the population to more prosperous places of residence. As a result of the analysis of the dynamics and structure of investments among territorial entities, it was found that the East Kazakhstan region, in terms of investments in fixed assets, in terms of their growth rates, belongs to the leading region in the country. Based on the SWOT analysis, the strengths and weaknesses, opportunities and threats to the investment attractiveness of the East Kazakhstan region were identified. This gave the basis for the characterization of the object under study as a promising region for investment, with significant investment potential with moderate investment risks. Relying on strengths, taking into account the impact of weaknesses and threats, without missing the available opportunities, it is possible to significantly increase the investment attractiveness of the region, attract foreign and domestic investors and thereby ensure financing of investment projects and programs, diversify the economy through the infusion of financial resources, solve the problem of employment and ensure sustainable development of the region. The heterogeneity of the economic development and investment space of Kazakhstan highlights the problem of smoothing interregional disparities and improving the quality of life of the population regardless of the place of residence, which is impossible without attracting investment to each region, developing an investment strategy taking into account local peculiarities.